2021
DOI: 10.1101/2021.06.30.450634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mega-fire in Redwood Tanoak Forest Reduces Bacterial and Fungal Richness and Selects for Pyrophilous Taxa and Traits that are Phylogenetically Conserved

Abstract: Mega-fires of unprecedented size, intensity, and socio-economic impacts have surged globally due to climate change, fire suppression, and development. Soil microbiomes are critical for post-fire plant regeneration and nutrient cycling, yet how mega-fires impact the soil microbiome remains unclear. We had a serendipitous opportunity to obtain pre- and post-fire soils from the same sampling locations because the 2016 Soberanes Fire, a mega-fire burning >500 Km2, burned with high severity throughout several of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 111 publications
(198 reference statements)
2
7
0
Order By: Relevance
“…In our system, phosphate was significantly lower in the burned sites (data not shown), thus potentially explaining the fruiting of Coprinellus at later successional stages. Moreover, in support of recent studies in pine forests (Carey et al, 2020;Enright et al, 2021;Pulido-Chavez et al, 2021), we found Geminibasidium in our burned soils. Geminibasidium is a recently described thermotolerant saprobe (H. D. T. Nguyen et al, 2013) that was not present in the unburned sites but dominated early successional stages.…”
Section: Pyrophilous Fungi Dominate the Burned Communities And Drive Successionsupporting
confidence: 93%
See 4 more Smart Citations
“…In our system, phosphate was significantly lower in the burned sites (data not shown), thus potentially explaining the fruiting of Coprinellus at later successional stages. Moreover, in support of recent studies in pine forests (Carey et al, 2020;Enright et al, 2021;Pulido-Chavez et al, 2021), we found Geminibasidium in our burned soils. Geminibasidium is a recently described thermotolerant saprobe (H. D. T. Nguyen et al, 2013) that was not present in the unburned sites but dominated early successional stages.…”
Section: Pyrophilous Fungi Dominate the Burned Communities And Drive Successionsupporting
confidence: 93%
“…In bacterial communities, succession and community turnover occurred rapidly and was initiated by aerobic, heterotrophic bacteria that form endospores and produce antibiotics. Consistent with previous studies, these genera belong to the phyla Acidobacteria, Actinobacteria, and Firmicutes (Enright et al, 2021;Whitman et al, 2019). Like plant successional patterns (Capitanio & Carcaillet, 2008;Egler, 1954), early successional stages were characterized by high bacterial diversity and a lack of dominance, mimicking the distributions observed in unburned communities.…”
Section: Pyrophilous Bacteria Dominate Burned Communities and Drive Successionsupporting
confidence: 87%
See 3 more Smart Citations